Inhibin B and ovarian function after total abdominal hysterectomy in women of reproductive age - Nahás, E. [UNESP]; Pontes, Anaglória [UNESP]; Traiman, Paulo [UNESP]; Nahas Neto, Jorge [UNESP]; Dalben, Ivete [UNESP]; De Luca, L. [UNESP] (My University, 2003)
The aim of this prospective study was to assess ovarian function using clinical and endocrine parameters in women of reproductive age who underwent total abdominal hysterectomy. Sixty-one women, aged ≤ 40 years, were allocated into two groups: group 1, consisting of 31 patients who had hysterectomy, and group 2, consisting of 30 normal women. Inclusion criteria were normal ovarian function at baseline, normal body weight, no hormonal diseases and basal follicle stimulating hormone (FSH) level of < 15 mIU/ml. FSH, luteinizing hormone (LH), estradiol and inhibin B levels as well as maturation value (MV) were measured by vaginal cytology on three occasions: baseline, and 6 and 12 months after hysterectomy. Analysis of variance, the Friedman test, Mann-Whitney test and t-test statistics were employed to compare the two groups. At baseline the groups were homogeneous. At months 6 and 12, hysterectomized women showed decreased median values of inhibin B, increased median values of estradiol (p < 0.05), unchanged median values of FSH and LH, and decreased median values of MV (p < 0.05). In the hysterectomy group, 12.9% (4/31) of the patients had FSH levels of > 40 mIU/ml, estradiol of < 20 pg/ml and inhibin B of < 5 ng/ml, compatible with ovarian failure. In the control group, all the parameters studied remained unchanged. These results suggest that total abdominal hysterectomy accelerates the decline in ovarian function in women of reproductive age.
Keywords: Hysterectomy; Inhibin B; Ovarian Function; Vaginal Cytology; estradiol; follitropin; inhibin B; luteinizing hormone; abdominal hysterectomy; adult; analysis of variance; body weight; controlled study; endocrine function; female; Friedman test; human; major clinical study; maturation; ovary function; priority journal; prospective study; rank sum test; reproduction; vagina cytology; Adult; Analysis of Variance; Case-Control Studies; Estradiol; Female; Follicle Stimulating Hormone; Humans; Inhibins; Longitudinal Studies; Luteinizing Hormone; Ovary; Prospective Studies